PENGARUH KINERJA PERUSAHAAN, CORPORATE GOVERNANCE, DAN KARAKTERISTIK EKSEKUTIF TERHADAP KOMPENSASI EKSEKUTIF - Suherman Suherman; Yoseph Y. P Pardede; Umi Mardiyati (Jurnal Keuangan dan Perbankan, 2016)
Abstract The objectives of this research are 1)to examine the effect of firm performance on executive compensation, 2)to investigate the effect of corporate governance on executive compensation, and 3)to find out the effect of execu-tive characteristics on executive compensation. Sample of this research consists of 46 firms (157 observations) listed on Kompas100 index between 2010 and 2013. Controlling for firm size, the results show that 1)ROA has positive and significant effect on executive compensation, but NPM and Tobins Q do not, 2)institutional ownership and independent commissioner do not have significant effect on executive compensation, and 3)ex-ecutive age and gender do not have significant effect on executive compensation.